Sosialisasi Pencegahan 3 (Tiga) Dosa Besar Pendidikan di SDN 9 Tumijajar - Arum Sulastri; Nur Amini (PT. Karya Inovatif Nusantara, 2025)
School is a second home for students, security and comfort must be guaranteed, however, it is possible that school is also a place that is less safe for students because of the three major sins in education such as sexual violence, intolerance and bullying which can affect the physical and psychological, thus hindering development. learners. The socialization on the prevention of the three big sins discusses how to prevent the Three Big Sins of Education, especially at SDN 9 Tumijajar, which can influence the world of education and have an impact on the future, which currently is not widely known by students. The methods used include lectures, PPT presentations, and question and answer sessions. The aim of implementing socialization on the prevention of the three major sins is to provide insight and knowledge regarding the three major sins in the world of education so that students can avoid and prevent the occurrence of the three major sins of education, especially at SDN 9 Tumijajar. As a result, students learn about the impacts of bullying, sexual violence and intolerance, as well as how to prevent them. This socialization involved 40 class V and VI students. The activity will be held on Wednesday, November 27 2024, face to face.